Development Of Atmospheric Pressure Plasma Jet In Air - Tyata, RB; Subedi, DP; Shrestha, A; Baral, D (Kathmandu University Journal of Science, Engineering and Technology, 2012)
In this paper, an atmospheric pressure plasma jet (APPJ) in air that is expected to be useful for polymer surface modification has been reported. The plasma jet was produced by applying (10 - 30) kHz, (0 - 20) kV AC source. The electrical and optical measurements have also been reported. The use of solenoid as an external electrode has been found to be more effective in boosting the jet to a distance up to 30 mm even with a small flow rate of air. The characteristic of the proposed APPJ was investigated by measuring the effect of treatment on a PE film on the jet for different exposition time and distance from the nozzle. It has been confirmed that the jet can modify polymer film with a work distance of over 25mm. This plasma jet can be useful for the treatment and cleaning of objects having large structures and could be used in wider areas of application. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6035 KUSET 2012; 8(1): 15-22